ELUCIDATING THE EFFECTS OF MUTATIONS IN Q209 OF GNA11 ON CELL APOPTOSIS IN HUMAN ADRENOCORTICAL CELLS - Long, Kha Chin; Sukor, Norlela; Tan, Geok Chin; Murad, Nor Azian Abdul; Brown, Morris Jonathan; Azizan, Elena Aisha (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Gain-of-function mutations, Q209H, Q209P and Q209L, of GNA11 were recently found to occur in CTNNB1 mutant aldosterone-producing adenomas (APAs). These mutations were also found to be present in the hyperplastic zona glomerulosa adjacent to the double-mutant APAs. This study aims to investigate the effects of GNA11 Q209 mutations on tumorigenesis through measurement of cell apoptosis in the human adrenocortical cell line, HAC15. METHODOLOGY HAC15 was transfected with GFP-tagged GNA11 Q209H, Q209L, Q209P or wild-type (WT) plasmids. To note, HAC15, a subclone of H295R cells, inherently has the CTNNB1 S45P mutation. 48 hours post-transfection, cell apoptosis was assessed using the Pacific Blue™ Annexin V/SYTOX™ AADvanced™ apoptosis assay (BD Biosciences, USA). The supernatants and cells were harvested for aldosterone and cortisol determination, and RNA isolation. RESULTS HAC15 cells transfected with GNA11 mutants, Q209H, Q209L and Q209P, had elevated aldosterone production compared to WT at 62.4% (p=0.001), 71.2% (p=0.001) and 59.5% (p=0.001), respectively. Cortisol production was only slightly elevated in HAC15 cells transfected with Q209H (19.7%, p=0.01) and Q209L (24.6%, p=0.01), compared to WT. CYP11B2 mRNA expression was also upregulated compared to WT by 3.5 folds (p=0.001) for Q209H, and around 8 folds (p=0.001) for Q209L and Q209P. Analysis of flow cytometric apoptosis assay showed GNA11 mutants did not affect cell apoptosis. CONCLUSION The findings suggests that GNA11 Q209 mutation increases aldosterone secretion of adrenocortical cells with no or little effect on apoptosis rate. Further experiments on cell proliferation are needed to rule out whether GNA11 Q209 mutations affects tumorigenesis.